Parents Taking on the Teachers’ Roles in Online Learning: A Case Study - Darman Fauzan Dhahir; Mukhlis Amin; Nfn Herman; Nfn Bahrawi; Yayat Dendy Hadiyat; Nfn Tasmil; Nur Alam; Emilsyah Nur (Jurnal Pekommas, 2021)
The Covid-19 pandemic forces education stakeholders to implement the online learning policy. They face challenges in Science, Technology, and Mathematics (STM) educations that are the most difficult subjects. Responding to the policy, parents may take on the role of teachers. This study explores the experiences of parents that take on the role of teachers, particularly in STM. The study uses a descriptive qualitative approach. Data obtained by interviewing several parents of students who were selected by convenience sampling method. Data were analyzed using Miles & Huberman’s interactive model regarding the grounded theory for concluding. It found that parents take the teacher's role as the resource provider, the supporter & learning facilitator, the mentor, and the personal model. Challenges were both technical and non-technical forms. Some of them do not master the subject matter of their children, making it difficult to provide support and take the role of a teacher. Some of them took the place of their children to work on assignments from school. Some others simply provide scaffolding to their children. Some of them use the internet to understand the subject matters or find answers, but some others could not.  This has implications on how parents should be prepared in implementing distance learning policies, especially in STM fields of study.